Royal tour - Alward, Amy (London: Simon & Schuster, 2016)
Since winning the Hunt and saving her new BFF, Princess Evelyn, Sam Kemi has been royally busy. What with TV interviews, working in her family's potion store and preparing to join Evelyn on her world tour, Sam still hasn't had time for a real date with Zain, her new-boyfriend-slash-former-rival. And that's not happening anytime soon. Someone has tampered with Sam's grandad's mind and she is the only one who can unlock his memories. Memories that contain the key to the most powerful potion in the world and one which people would kill for. So Sam must swap dresses, princes and palaces for dragons, centaurs and caves in her quest to save her grandad (and everyone
Keywords: Young adult fiction